Peningkatan Pengetahuan Ibu Hamil Tentang Perawatan Preeklamsi Awitan Dini Dengan Bumil Bahagia - Erlina Lutfiayu Pratiwi; Dwi Pangesti, Wilis; Ina Rahayu Sakti (NERSMID : Jurnal Keperawatan dan Kebidanan, 2024)
Pregnancy with early onset preeclampsia (EOP) accounts for 2-10% of maternal and fetal mortality worldwide. One of the factors causing high mortality is the lack of knowledge of pregnant women about caring for pregnancies with a risk of EOP. Efforts to increase knowledge of pregnant women through various media are necessary in antenatal care programs, including the Bumil Bahagia application. This study aimed to determine the relationship between the use of the Bumil Bahagia application and the level of knowledge regarding EOP high-risk pregnancy care. This research is a quantitative study with a pre-experimental one-group pretest and posttest design. The research was carried out at Kembaran I and Sokaraja I Community Health Centers in Banyumas Regency. The research sample consisted of 54 people who used the purposive sampling technique. Data analysis was performed using the Wilcoxon test to determine the increase in knowledge. The research results show that there is a relationship between the use of the Bumil Bahagia application and increased knowledge (p-value < 0.001). The difference in the proportion of pregnant women who used the Bumil Bahagia application and those who did not was 31.4%. The use of the Bumil Bahagia application has direct implications for pregnant women in prenatal care, especially for mothers at high risk of EOP. This application can also be used as a health-promotion medium by health workers in pregnancy care.